Risk assessment based on driving behavior for preventing collisions with pedestrians when making across-traffic turns at intersections - Hiroshi Yoshitake; Motoki Shino (IATSS Research, 2018)
Traffic accident statistics in Japan show the necessity of preventing vehicle-on-pedestrian accidents. If the risk of a vehicle colliding with pedestrians could be evaluated in advance, driver-assistance systems would be able to support drivers to avoid potential collisions. Here, features of driving behavior and methods for assessing the risk of collision were investigated for a right turn at an intersection in left-hand traffic, which is a typical vehicle-on-pedestrian accident scenario. The results showed that pedestrian-collision risk can be evaluated from how the driver slows the vehicle and where the driver looks while turning during the maneuver. Moreover, pedestrian-collision risk could be predicted based on driving behavior upon commencement of steering when making an across-traffic turn. Keywords: Risk assessment, Driving behavior, Pedestrian collision, Across-traffic turn